2021
DOI: 10.3390/v14010069
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Potent Fusion Inhibitors with Potential Pan-Coronavirus Activity That Effectively Inhibit Major COVID-19 Variants of Concern (VOCs) in Pseudovirus-Based Assays

Abstract: We report the discovery of several highly potent small molecules with low-nM potency against severe acute respiratory syndrome coronavirus (SARS-CoV; lowest half-maximal inhibitory concentration (IC50: 13 nM), SARS-CoV-2 (IC50: 23 nM), and Middle East respiratory syndrome coronavirus (MERS-CoV; IC50: 76 nM) in pseudovirus-based assays with excellent selectivity index (SI) values (>5000), demonstrating potential pan-coronavirus inhibitory activities. Some compounds showed 100% inhibition against the cytopath… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…We conclusively established the structure-activity relationship (SAR). We demonstrated that despite the presence of the same ene-rhodanine moiety in the compounds used as controls, they showed no antiviral activity at all 46 . We were confident about the SAR information from that study and used that to search compounds from commercial small molecule drug-like databases.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…We conclusively established the structure-activity relationship (SAR). We demonstrated that despite the presence of the same ene-rhodanine moiety in the compounds used as controls, they showed no antiviral activity at all 46 . We were confident about the SAR information from that study and used that to search compounds from commercial small molecule drug-like databases.…”
Section: Resultsmentioning
confidence: 87%
“…Peptide-based pan-coronavirus fusion inhibitors were recently shown to possess potent inhibitory activity against HIV-1, HIV-2, and SIV 45 . These encouraging results motivated us to screen a set of COOH-containing molecules, which we referred to as NBCoVs and tested them against SARS-CoV-2, SARS-CoV, and MERS-CoV in spike-pseudotyped antiviral assays 46 . However, the NBCoV molecules contain an ene-rhodanine scaffold, a well-known frequent hitter, which suggests that they might be pan assay interference compounds (PAINS) 47-49 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations